Exploration of the global commerce: A comprehensive review of international trade and foreign trade - Aranibar-Ramos, Edgar Romario (2023)
The cross-border exchange of goods, services, capital, and knowledge has emerged as a crucial driver of economic prosperity. Consequently, the objective of this work is to provide an overview of research trends in foreign and international trade, identifying thematic gaps and outlining areas for future research. To achieve this, a scientometric analysis and a systematic review of literature on the production of Scopus were carried out in the last five years. The findings revealed significant growth in current production, in which information was predominantly in English. Similarly, policy formulation requires a comprehensive approach, with a balance between free markets and protectionism, and an encouragement of participation in trade agreements and free trade agreements that drive multilateral and bilateral integration. Additionally, investments in infrastructure, logistics, and technological innovation, along with an understanding of socioeconomic, cultural, health, and environmental factors, allow for the improvement of connectivity and efficiency in international trade. Nonetheless, considering the environmental impact of trade, trends that aim to strike a balance between trade and environmental conservation, as well as addressing socioeconomic inequality, have emerged.